Development of a bio-electrospray system for cell and non-viral gene delivery. Issue 12 (9th February 2018) - Lee, Myung Chul; Seonwoo, Hoon; Garg, Pankaj; Jang, Kyoung Je; Pandey, Shambhavi; Kim, Hong Bae; Park, Sang Bae; Ku, Jong Beom; Kim, Jang Ho; Lim, Ki Taek; Chung, Jong Hoon
Abstract : The NVG-BES system facilitated to introduce DNA to cells and delivered cells to a target simultaneously. In this method, a cationic polymer was used as non-viral carrier with electric force by bio-electrospray (BES) system to electrospray living cells onto a target. Abstract : Bio-electrospray technology is a very attractive tool for preparing scaffolds and depositing desired solutions on various targets by electric force. In this study, we focused on the application of a bio-electrospray (BES) technique to spray cells on the target and to simultaneously deliver genetic constructs into the cells, called non-viral gene delivery-based bio-electrospray (NVG-BES). Using this method, we tried to harvest the electric charge produced during electrospray for the cellular internalization of cationic polymer/DNA nanoparticles as well as the delivery of living cells on the desired substrate. Furthermore, we optimized the voltage, culture medium and polymeric cationic charges for high transfection efficiency and cell viability during NVG-BES. As a result, the solutions used during the NVG-BES process played an important role in improving transfection efficiency. We determined that a voltage of 10 kV with PBS as the spraying solution showed high transfection efficiency, probably due to the facilitation of cationic polymer/DNA nanocomplexes in cellular internalization and their subsequent expression. In conclusion, NVG-BES, as a novel method, is expected to deliver genes to cells and simultaneously deliver transfected cells to any substrate or scaffold.